The influence of emotional intelligence while buffer effect on stress - Cruz, Catarina (2019)
Introduction The rise of new technologies and globalization leads tend to a people management valuing the skills of emotional intelligence (EI) expressed. This assumes a positive impact on people management, especially in health care. Objective The present study aimed to clarify the relationship of IE with the perceived stress (PS) in the management of people, in particular in health professionals. Methods Integrative review of literature. The question of departure [in relation to healthcare workers (P), how EI acts as buffer effect (I) in PS (C) in your workplace (O)], contributed to the definition of the inclusion criteria. The selection of the articles followed the guidelines according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta- Analyses) and indexed in the databases CINAHL, MEDLINE, Nursing & Allied Health, B-On, with a time horizon from 2011 to 2017. The final sample consisted of 14 eligible articles from different countries. Results The eligible studies reveal that IE presents a moderating effect on the relationship stress/ burnout, with greater evidence in professions that require greater emotional involvement, as health workers. The analysis showed that managers, to make the team your invincible, should adopt strategies that enhance the reduction of PS employee and, at the same time, encourage participation in training programmes for development of EI. Conclusion We conclude that emotional intelligence can have an impact on the health of organizations, to the extent that employees with higher values of emotional intelligence are more effective to manage your emotions and also the emotions of others, What makes them proactive people and which will enhance productivity-enhancing, as are leaders among their peers. Keywords , perceived stress, people management